Improving Students’ Higher Order Thinking and Environmental Attitudes through Implementation of Teaching Materials Based on Scientific Literacy and Conservation (Journal of Innovative Science Education, 2020)
Higher Order Thinking (HOT) ability and environmental attitudes was needed in facing challenges, demands, and the rapid development in the 21st century. Conditioning students in learning requires good teaching materials in accordance with students’ need and global demans, current or future. One of the teaching materials needed was content-based on scientific literacy and conservation. The purpose of this study was (1) to analyze the improvement of HOT ability and environmental attitude of students through the implementation of teaching materials based on scientific and conservation literacy. (2) to analyze the differences of improving students’ Higher Order Thinking Ability and environmental attitudes using scientific-based literacy and conservation as the teaching materials and not using it. This research was an experimental study conducted by pretest-posttest and group control design. The reseach subject was 30 students in grade VIIC (experimental group) and 30 students in VIIA grade (control group) in SMP N 1 Kaliwiro. We used written test to gather students’ HOT ability improvement, and Likert scales for students’ environmental attitude data. The data analysis technique used was using the N-gain test and t-test. The results of the study obtained that N-gain value of the experimental group on the aspect of Higher Order Thinking ability 0.70, the control group 0.40 which has the results of the t-test -7.83. The results of the environmental attitudes obtained the N-gain value of the experimental group 0.50 and the control group 0.18 which has the results of the t-test -7.19. The results showed that teaching materials based on scientific literacy and conservation can be used to improve Students’ higher order thinking ability and environmental attitude.